<span>jika xy = 0 , kemudian menganggap x dan y = 0
faktor 2x^2-9+7
(2x-2)(x-7)=0
2x-2=0
2x=2
x=1
x-7=0
x=7
</span><span>jika 1 = x1 dan 7 = x2 maka jawabannya adalah 1^2+7^2-4(1)(7)=22
</span>
jika 7 = x1 dan 1 = x2 maka jawabannya adalah
7^2+7^2-4(7)(1)=22
<span>jawabannya adalah 22</span>
Answer:
6 to the power of 2.
Step-by-step explanation:
Recall that whenever you divide exponents with the same base, you subtract the powers, but the base will still be the same. Therefore, 6 to the power of 12 divided by 6 to the power of 10 is 6 to the power of 2. Subtract the powers (exponents) or 12 minus 10, and you get 2. Since the base doesn't change, it is still 6. The solution to this expression is 6 to the power of 2. Hope this helps!
You would do 2 · 26 · 26 = 1,352 different arrangements